(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2018)
Interpolyelectrolyte complexes, which constitute a type of polymeric material obtained through the selfassembly of oppositely charged polymers, exhibit interesting properties for use in the design of smart matrices for drug delivery. In the present study, a stoichiometric interpolyelectrolyte complex (SIPEC) composed of Eudragit E® and Eudragit® L100 was obtained at pH 6.0 and characterized and evaluated as a hydrophilic matrix for dexibuprofen. The formation of a SIPEC was monitored by ζ-potential measurements and characterized using infrared spectroscopy, thermal analysis, and scanning electron microscopy. The results indicated that a SIPEC obtained under these conditions can be used as a matrix for controlling the release of dexibuprofen and exhibit a pH-triggered release.